Multi-Objective Optimization Algorithms Design based on Support Vector Regression Metamodeling - Qi Zhang; Guangchun Yang; Rui Tang; Guoqi Xiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to solve the multi-objective optimization problem in the complex engineering, in this paper a NSGA-II multi-objective optimization algorithms based on Support Vector Regression Metamodeling is presented. Appropriate design parameter samples are selected by experimental design theories, and the response samples are obtained from the experiments or numerical simulations, used the SVM method to establish the metamodels of the objective performance functions and constraints, and reconstructed the original optimal problem. The reconstructed metamodels was solved by NSGA-II algorithm and took the structure optimization of the microwave power divider as an example to illustrate the proposed methodology and solve themulti-objective optimization problem. The results show that this methodology is feasible and highly effective, and thus it can be used in the optimum design of engineering fields. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2628